Evaluation of herbicides for control of weeds in chilli (Capsicum annuum) - Singh, Rajender; Jangir, R P; Poonia, B L (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during the rainy season of 1991 and 1992 to evaluate 4herbicides for the control of weeds in chilli (Capsicum annuum L.). All weed-controltreatments reduced density and dry matter of weeds infesting chilli field exceptmetolachlor@ 0.5-1.0 kg/ha, which was found ineffective on broad-leaf weeds. Out of the 4herbicides, pendimethalin@ 1.0 kg/ha was found most effective (87.3%) on grassy weeds,followed by metolachlor @ 1.0 kglha (80.0%) and oxyfluorfen @ 0.3 kg/ha (73.4%). However,best control of the broadÂ·leaf weeds was achieved by oxyfluorfen@0.3 kg/ha (92.0%), followedby its lower dosages (0.1-0.2 kg/ha) and pendimethalin @ 1.0 kg/ha (74.4%). Oxyfluorfen @0.3 kg/ha showed improvement in crop growth and fruits/plant, giving the maximum dry-chilliyield (2 210 kg/ha) compared with the other weed-control treatments.